2014
DOI: 10.1158/1055-9965.epi-14-0240
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Health Reduces Risk of Obesity-Related Cancer in Framingham Study Adults

Abstract: Background It is unknown whether the risk for obesity-related cancers between metabolically unhealthy and healthy overweight/obese adults. Methods Data on body mass index (BMI), waist circumference (WC), waist-to-height ratio (WHtR), and random blood glucose in Framingham Heart Study adults (n=3763) ages 55-69 were used to estimate risks of obesity-related cancers (n=385) including post-menopausal breast, female reproductive, colon, liver, gallbladder, pancreas, and kidney cancers, as well as esophageal aden… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
88
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 88 publications
(95 citation statements)
references
References 32 publications
3
88
2
Order By: Relevance
“…Relevant studies have shown that obese populations with high blood sugar levels have almost double the risk of developing obesity-related cancers, while obese populations with normal blood sugar levels only carry a 50% increased risk of developing cancers. In addition, metabolic dysfunction also increases the risk of cancer in obese individuals (15). In the present study, CRC was induced in rats using DMH.…”
Section: Discussionmentioning
confidence: 72%
“…Relevant studies have shown that obese populations with high blood sugar levels have almost double the risk of developing obesity-related cancers, while obese populations with normal blood sugar levels only carry a 50% increased risk of developing cancers. In addition, metabolic dysfunction also increases the risk of cancer in obese individuals (15). In the present study, CRC was induced in rats using DMH.…”
Section: Discussionmentioning
confidence: 72%
“…Chronic inlammation is thought to provide one such pathway. In recent analysis of Framingham Study adults, Denis has shown that "metabolically healthy obese" adults, who have atenuated inlammatory proiles, also appear to be protected from certain obesity-associated cancers [5,10].…”
Section: Discussionmentioning
confidence: 99%
“…Obesity is an alarming epidemic because of its comorbidities, which include diabetes, cardiovascular disease [4], and based on new evidence, increased risk of some forms of cancer [5,6]. Obesity-driven diabetes, or Type 2 diabetes, was previously only a problem for adults and was termed "adult-onset" diabetes, to distinguish it from "childhood" diabetes, or Type 1 diabetes, which is primarily immunological in origin.…”
Section: The Pediatric Obesity Epidemic Global Inequality and Currmentioning
confidence: 99%
“…How obesity factors in with other modifiable factors such as physical activity and diet in terms of increasing or decreasing the risk of colon cancer, respectively, are important observations [24][25][26]. However, it is not just the BMI or obesity or being underweight that are solely responsible; but likely more so the dynamic changes in weight with time in patients with metastatic colorectal cancer that are likely to be playing a role and reflective of other comorbidities and nutritional status in this patient population.…”
mentioning
confidence: 99%
“…Incorporating surrogate radiological measures is also an accurate and cost-effective method, as patients with colon cancer might receive several CT scans during the course of their disease [30,32]. Furthermore, it is important to note that a proportion of overweight/obese patients may still be 'metabolically healthy' (normal glucose tolerance, lipid levels, and blood pressure as well as less ectopic fat) compared with those with 'metabolic dysfunction,' with overall higher risk and poorer outcomes in the latter group [26].…”
mentioning
confidence: 99%